Educational Wastage At Vocational Training Institutions In El Oued Province: Quantitative Analytical Study Of Statistical Indicators Of The Phenomenon - Tichabet, Yasmina; Tarzoult Amrouni, Houria (University of Eloued جامعة الوادي, 2016)
Vocational training sector is one of the most important tools of the country for the preparation of human capital and the development of individual skills, especially that the latter is among the significant mechanisms of activating economic growth of each society. Despite its importance, vocational training encounters various obstacles that prevent achieving its aims on the individual and the community levels so that it would result in prosperity and progress of the society. One of these obstacles is the phenomenon of educational wastage. Thus, the present study tried to investigate educational wastage at vocational training institutions in El Oued Province (south-east of Algeria) during the period (2013-2015). Results are displayed in tables for easy to read, followed by analyze qualitative analysis for these results. إن قطاع التكوين المهني هو من بين أهم وسائل الدولة إلعداد الرأس المال البشري وتنمية مهارات الفرد، خاصة وأن هذا األخير يعد من أهم ميكانيز مات تفعيل التنمية االقتصادية لكل مجتمع، ورغم أهميته نجد أن هناك بعض المعيقات التي تحول دون تحقيقه ألهدافه على الفرد وعلى الجماعة بما يعود على المجتمع والمؤسسات والدولة من ازدهار وتقدم، ومن أهم هاته المعيقات ظاهرة الهدر التربوي، فجاءت هذه الدراسة لتسليط الضوء علي الهدر التربوي في مؤسسات التكوين المهني بإحدى واليات الجنوب الشرقي الجزائري أال وهي والية الوادي وذلك بمعرفة حجم الهدر فيها في ثالث سنوات االخيرة "0222-0222- 0222 ،"وسنقوم بعرض نتائجها في جداول لتسهيل قراءتها، وفي األخير سنقوم بتحليل النتائج تحليال كيفيا.
الهدر التربوي بمؤسسات التكوين المهني في ولاية الوادي : دراسة كمية تحليلية للمؤشرات الإحصائية للظاهرة
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: educational wastage-Vocational training- Trainees; الهدر التربوي - مؤسسات التكوين المهني – المتربصين